The future of American agricultural competition - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1883)
In this paper I shall endeavour to bring before the members of the Statistical Society some figures, which seem to me to throw considerable light on the vexed question of the extent to which farming in the United Kingdom is likely to be affected by foreign competition, especially that of the United States of America. For some years past we have been constantly warned of the great danger with which our agricultural interests are threatened by the importations of food supplies. The friends of the farmer prophesy his ruin as the inevitable result.
Read before the Society, 12 December 1882
Keywords: American agriculture; International trade; Competition; 314.15